Characterisation and Modelling of Manufacturing–Microstructure–Property–Mechanism Relationship for Advanced and Emerging Materials (Basel MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of papers published in a Special Issue that collected the recent advances within and investigations of the research fields of manufacturing and the characterisations or modelling of materials. The variety and quality of all these papers are addressed to both academic and industrial researchers who are looking for new information that can contribute to the advancement of future research in these highly challenging fields.
English
Keywords: History of engineering & technology; Technology: general issues; 316L SS; 3D optical scanning; AA2011-T6; AA6082-T6; Al-Si + Y2O3 coating; aluminum alloys; annular plate; ATIG welding; AZ91D magnesium alloy; brittle fracture; characteristic impedance; characterization parameter set; compressive strength; computational fluid dynamics; corrosion resistance; Cowper-Symonds model; data transmission over textiles; depressurization; dislocation nucleation; dynamic deformation behavior; e-textiles; evolution of microstructure; face gears; free vibration; free vibration analysis; friction stir deposition; friction stir spot welding; genetic algorithms; grain refinement; Hall-Petch relationship; hydrogen; hydrogen embrittlement; hydrogen fuel cell; improved Fourier series; intergranular deformation; ISO25178; keyhole refilling; laminated composite double-cylindrical shell system; laminated composite shell; laminated submarine-like model; laser cladding; lightweight structures; loaded tooth contact analysis; magnesium alloy AZ91; manufacturing and processing; mathematical modeling; mechanical properties; meshfree method; microstructure; mixing design method; molecular dynamics; morphological characterization; n/a; nanograined materials; numerical model; orifice plate structure; parametric design; particle swarm optimization (PSO)